Film as communicational mediation of the ecological crisis - Bert Olivier (Communicare)
This paper is a communication-oriented, ecological interpretation of James Cameron’s recent film, Avatar, and of John Hillcoat’s The Road – two films that address the current global ecological crisis very differently. By ‘ecological’ is meant that – in the case of Avatar – the film is ecologically significant in its stressing of the vital interconnectedness of all living beings both with one another and with their inorganic environment. The question of how this ecological stance is cinematically articulated in Avatar, in science-fictional terms, is all important, because a communicational failure in this regard would fall short of imparting to audiences the potential outcome of the continuing destruction of ecosystems, comparatively speaking, on Earth. In The Road the ecological dimension is encountered very differently, because the cinematic-communicational means employed function in a register at odds with that utilised in Avatar. The point of this paper is to explore the communicational differences, including the one regarding cinematic-communicational register, between the two films, regardless of the fact that, arguably, they promote the same ecological insights.